Pendampingan Revitalisasi Bumdes Amanah Mandiri Desa Jatimukti, Kabupaten Sumedang, Provinsi Jawa Barat - Sari, Agni Grandita Permata (PT. Riset Press International, 2024)
This article discusses the revitalization of the Village-Owned Enterprises (BUMDes) Amanah Mandiri in Jatimukti Village, Jatinangor Subdistrict, Sumedang Regency. The aim of this community service was to reactivate the previously inactive BUMDes through a series of activities held from June 3 to 6, 2024, including participatory FGDs, education on BUMDes and village potential mapping, and simulation and assistance in organic fertilizer production. Methods employed included FGDs, training sessions, simulations, and participatory dialogues with various stakeholders. This community service was collaboratively conducted by involving agricultural advisors from Sumedang Regency. The main findings indicate that integrated participatory approaches and education effectively stimulate interest and economic activities within BUMDes, particularly through innovative organic fertilizer products. The conclusion drawn from this study is that with the right approach, BUMDes can serve as the backbone of village economies, enhance community welfare, and reduce farmers' dependency on chemical fertilizers.